Export Performance Under Environmental and Political Frictions: Evidence From Indonesia - Jagat Prirayani; Ana Noveria (Publikasi Indonesia, 2026)
This study examines how environmental quality and political stability shape Indonesia's export performance, focusing on interactions among macroeconomic, environmental, and institutional factors. While traditional export models emphasize economic growth and exchange rate effects, this paper argues that these factors alone cannot fully explain export outcomes given growing environmental constraints and institutional complexities. Using annual data from 1996 to 2023, the research applies multiple regression models to assess direct, nonlinear, and interactive effects of key variables, including GDP, carbon emissions, political stability, and exchange rate fluctuations. The empirical findings highlight three key points. First, economic growth consistently emerges as a strong and significant driver of export performance, underscoring the role of domestic productive capacity. Second, the relationship between environmental pressure and exports is nonlinear; initial industrial expansion tends to boost exports, but excessive carbon emissions can undermine long-term competitiveness. Third, environmental concerns appear to diminish the effectiveness of exchange rate depreciation, indicating a conditional limit on macroeconomic policy. Fourth, political stability does not directly affect exports but significantly shapes how exchange rate changes influence them, underscoring the importance of institutional quality as an enabling factor. Overall, the findings indicate that export performance results from a complex interplay of macroeconomic fundamentals, environmental conditions, and institutional factors. Policy-wise, the results suggest that export promotion should go beyond traditional methods focused on growth and exchange rate policies and should also include environmental improvements and institutional capacity-building.